From modern “style” to modern architecture: meanings of modern in the brazilian magazines a casa and arquitetura e urbanismo (1923- 1942) - Nery, Juliana Cardoso (Universidad del Bío-Bío, Chile, 2016)
This article is based on research that analyzed a corpus of 225 issues of the magazines A Casa and Arquitetura e Urbanismo published between 1923 and 1942. It sought to identify transformations in meaning and forms of expressing that which is modern through the texts and images published. The objective was to understand how this term that encompasses a wide variety of expressions became a hegemonic tendency clearly defined in Brazilian architecture, which even accep- ted the name Modern Movement in order to be identified. The modern “style” appears in Brazilian magazines beginning with the 1925 International Exhibition of Modern Decorative and Industrial Arts in Paris, where different architectural displays were presented that were indistinctly identified as “modern” in the magazines analyzed. Ignored by most his- torical narratives, these varied expressions of modernity were responsible for conquering and fertilizing –largely due to the publication of specialized periodicals– a dry field in which would later flourish the exceptional and nationally and internationally celebrated works of modern Brazilian architecture with a Corbusian base.